Effects of Sago starch concentration on direct lactic acid production by enterococcus faecium no 78 - Siti Nasirah, Bt. Abd Wahab. (Universiti Malaysia Sarawak (UNIMAS), 2006)
This study was performed to study the effects of different sago starch concentration on the production of lactic acid by Enlerococcus jaecium no 78. Enlerococcus jaecillm No 78 is an amylolytic lactic acid bacteria (ALAB) which is capable of directly hydrolyzing starch as their carbon source. Four different concentrations were studied, 15 giL, 20 giL, 30g/L, 40glL. Batch fermentation system was performed throughout this study. Besides determining lactic acid production, reducing sugar analysis, starch degradation analysis and viable cell count were also analyzed. Maximum lactic acid production, 10.62 giL was obtained when 30 gIL sago starch concentration utilized. Result for starch degradation analysis was too low than expected regardless of the sago starch concentration used. Maximum result obtained for this analysis was 21.55 gIL at 40 giL sago starch concentration. For viable cell count, highest result recorded was 10gIO 11.67 with 20 gIL sago starch concentration. Keywords: Ellterococcus jaecium No 78, amylol.ytic